ANDROID-BASED EDUCATIONAL APP FOR LEARNING THE PRAYER PROCESS - Eldo, Handry; Adrie Admira, Tb. M.; Sidik, Jafar; Fatmayati, Fryda (Journal of Information Systems Management and Digital Business, 2023)
Prayer is one part of prayer. There are several obligatory prayers for Muslims: morning, noon, Asar, Maghrib, and Isha. By following the development of mobile technology, prayer learning applications can be developed to be used anywhere and at any time without an internet connection. Android is a Linux-based mobile operating system designed by Android. Various activities can be done using a smartphone, such as working, playing, entertaining, and studying. Using multimedia development, it is hoped that users will be interested in learning how to pray. The application developed includes several pages containing material evidence, pillars, preparation, and prayer guides.